Immobilized metal ion chromatographic (IMAC) determination of ovomucoid in hen's egg white - A. Prošková; J. Kučera (Czech Journal of Food Sciences, 2002)
An immobilized metal ion high-performance liquid chromatographic technique was developed for the determination of one of the egg allergens - ovomucoid - in egg white and food products containing egg white. The method was tested using standard samples as well as complete egg white and its reproducibility was determined. The possible application of this method is discussed. The method is based on the HPLC chromatography on the chelating column saturated with copper ions. The sample is applied to the column at pH 7.5 and eluted isocraticaly with a buffer containing 1.75 mM imidazole in the optimum case.